The Knoxville News-Sentinel, Tenn., Sam Venable column - Venable, Sam (McClatchy - Tribune Business News, 2012)
[...]I'm afraid that mentioning this or any other private region in the context of Tennessee lawmaking will cause a new round of sweaty palpitations to break out -- like what occurred a few days ago as the state House debated the legal definition of "intimate parts."